From Theory to Practice: A Mathematics Pre-service Teachers’ Pedagogical Practice Dilemma - David Wafula Waswa (International Journal of Social Sciences & Educational Studies)
There are many theories on how students acquire knowledge and how instructions should be conducted in the classroom. Research has presented clear instructional strategies appropriate for students in diverse circumstances. However, most of these instructional strategies are not implemented in the classrooms. This research aims to investigate the gap between theory presented in the lecture rooms and actual teaching in the schools, and to examine the effect of this disconnect on the pre-service teacher. Data was collected through questionnaires answered by students from 11 universities in Kurdistan, Iraq. Results indicate the existence of a gap between theories in the lecture halls and actual practice in classrooms. Perceived insufficient time for instructors, actual insufficient time allocated to the practicum course, broad curriculum, cultural influences, and inadequate qualified and experienced mentor teachers are some of the suggested reasons for the missing link between theory and practice. Recommendations for stakeholders and suggestions on the way forward are discussed.